GEOLOGI DAN ALTERASI HIDROTERMAL DAERAH BANTAR KARET DAN SEKITARNYA, KECAMATAN NANGGUNG, KABUPATEN BOGOR, PROVINSI JAWA BARAT - Rizal Dwi Febriyana; Yoga Aribowo; Dian Agus Widiarso (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Alteration type at zone of mineralization has its own properties and characteristics that often characterized by the presence of mineral assemblage. The existence of alteration zone occurred due to changes mineral composition of rocks as a result of interaction between fluida of hydrothermal and wall-rocks. Alteration of hydrothermal is very closely linked with mineralization. Mineralization is an assembly and accumulation process of valuable rare minerals in the rocks to form ore deposits. Geological studies related to the characteristics and distribution of alteration and mineralization will assist in the planning of exploration process in the area. The aim of this study is to know the condition of geological research area that include variation of morphology, stratigraphy, structural of geology, alteration types are develop in the study area, as well as the relationship between altered minerals the result of hydrothermal alteration to precipitate epithermal mineralization in the study area.The methods used in this study include field mapping, followed by the method of sample analysis. Method of field mapping carried out by observing the lithology, structural of geology, geomorphology and alteration at Bantar Karet and surrounding areas, Nanggung subdistrict, Bogor Regency, West Java . Method of analysis carried out by analysis of petrology, petrography, mineralgraphy , X - ray diffractometer and the structure analysis of the lineament pattern.Lithology of the research area, beginning Early Miocene with sequence from old to young are unit of laminated tuff, unit of volcanic breccia, unit of andesite lava, unit of lapilli tuff, unit of tuff and unit of dacite intrusion. Structural of geology that develop in the study area are joint, fault that related with the lineament pattern, the main direction are Southwest-Northeast and Northwest-Southeast. Geomorphology of the study area was divided into two : the unit of volcanic landforms are very steep mountains and the unit of volcanic landforms are steep hilly. Alteration zones are contained in the study area, becoming three zones, there are Chlorite ± Smectite Alteration Zone (Propylitic), Smectite Alteration Zone - Kaolinite ± Montmorillonite (Argillic) and Silicified Zones. The mineralization exist are dessiminated Pyrite as ore mineral and oxide mineral such as Hematite which is the alteration of Magnetite and Feromagnesian on temperature conditions < 260oC. Characteristics of deposition types that developed in the study area based on the identification of geology, included alteration and mineralization is low sulphidation epithermal.